2015
DOI: 10.5056/jnm15036
|View full text |Cite
|
Sign up to set email alerts
|

Three Gaseous Neurotransmitters, Nitric oxide, Carbon Monoxide, and Hydrogen Sulfide, Are Involved in the Neurogenic Relaxation Responses of the Porcine Internal Anal Sphincter

Abstract: Background/AimsThe internal anal sphincter (IAS) plays an important role in maintaining continence and a number of neurotransmitters are known to regulate IAS tone. The aim of this study was to determine the relative importance of the neurotransmitters involved in the relaxant and contractile responses of the porcine IAS. MethodsResponses of isolated strips of IAS to electrical field stimulation (EFS) were obtained in the absence and presence of inhibitors of neurotransmitter systems. ResultsContractile respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Nitric oxide (NO) plays a prominent role in inhibitory NMT in the IAS of all species studied including man. 15,45,93,[123][124][125] Although the IAS lacks a myenteric plexus there are numerous varicose nicotinamide adenine dinucleotide phosphate/nNOS neurons located within the circular muscle layer. 15,16 Since first proposed in 1996, a number of studies have provided evidence that ICC-IM participate in nitrergic NMT in GI muscles.…”
Section: Nitrergic Inhibitory Motor Innervationmentioning
confidence: 99%
“…Nitric oxide (NO) plays a prominent role in inhibitory NMT in the IAS of all species studied including man. 15,45,93,[123][124][125] Although the IAS lacks a myenteric plexus there are numerous varicose nicotinamide adenine dinucleotide phosphate/nNOS neurons located within the circular muscle layer. 15,16 Since first proposed in 1996, a number of studies have provided evidence that ICC-IM participate in nitrergic NMT in GI muscles.…”
Section: Nitrergic Inhibitory Motor Innervationmentioning
confidence: 99%
“…McDonnell et al [ 60 ] reported that a purinergic pathway significantly contributes to inhibitory motor innervation in the IAS by hyperpolarization of the postjunctional membrane to produce inhibitory junction potentials. Folasire et al [ 61 ] also reported that hydrogen sulfide possibly contributes relaxation of the porcine IAS, and its potency is lower than that of CO. In addition, recombinant hemoglobin 1.1 (rHb1.1) could be caused specific obliteration of NO-induced relaxation of the IAS [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among other molecules recognized as NTs, there can be enumerated purines, such as adenosine triphosphate (ATP) [ 64 ], soluble gases (known as gasotransmitters), such as carbon monoxide (CO) [ 65 , 66 ], nitric oxide (NO) [ 65 , 66 ], and hydrogen sulfide (H 2 S) [ 66 ], and various neuropeptides [ 8 , 9 ], including somatostatin [ 67 ], β-endorphins [ 68 ], vasopressin [ 69 ], neurotensin [ 70 ], substance P [ 70 ], and neuropeptide Y [ 71 ]. One representative example from each category was chosen and briefly discussed.…”
Section: Neurotransmittersmentioning
confidence: 99%